Application Of The Principles Of Village Financial Management: Case Study of Jatiroto Village Lumajang - Setyobakti, Moh. Hudi (Jurnal Ilmu Manajemen Advantage, 2017)
Law No. 6 of 2014 on Villages, provides an important position for the village to play its role in development. The important role of the village is the local authority possessed by the village in managing its household. Urgency of the implementation of village authority in village development main flow lies in the ability of village financial management. The form of self-reliance of village management among others is the application of the principle of the principle as set forth in the regulation, as regulated in Permendagri 113 of 2014. This study aims to identify and analyze the application of the principles of village financial management, including; Principles of Transparency, Principles of Accountability, Principles of Participation, Orderly Principles and Budgetary Discipline. The type of research used in this research is descriptive qualitative and case study, application of village management principle in certain village. Locations in Jatiroto Village Jatiroto District Lumajang District with participants from the Village Head, Village Secretary, Village Treasurer, Implementation Team, Village Assistant, BPD and Community Leaders The results show the implementation of Jatiroto village financial management as follows; (1) The application of the principle of transparency has generally been implemented, although it needs to be optimized with media enrichment. (2) Accountability of village financial management is quite good, but there are some things that need to be strengthened, and improve management performance. (3) The management of village finances in Jatiroto village is quite participatory, some of the things that demonstrate this principle is the involvement of the community in the process of running activities, although it still needs to be improved, (4) The application of orderly principles and budgetary discipline, is basically already underway in every stage of village financial management that is run, some obstacles due to technical problems, such as facilities, competencies, and workload